Can selfies trigger social anxiety? A study on the relationship between social media selfie behavior and social anxiety in Chinese youth group - Liu, Yixuan; Zhu, Jiayu; He, Jianping (Frontiers in Psychology, 2022)
As modernization continues to advance the development of digital society, social media has become an important part of people's daily life and an extension and expansion of real social interactions. In this process, social media use and individual social psychology have increasingly become the object of academic attention, among which the relationship between selfie behavior, as an important interaction practice of youth group in social media, and social anxiety needs to be further explored and discussed. The purpose of this study is to investigate the current situation of selfie behavior, body image, and social anxiety among young people in China. Using a combination of qualitative and quantitative empirical methods, a questionnaire survey was conducted in Chinese mainland (n=920) to examine the mediating effects of social comparison and body image on social media selfie behavior and social anxiety, and found that there was a significant negative relationship between youth social media selfie behavior and social anxiety, while the serial mediating effects of social comparison and body image were significant. The findings of the study provide new ideas and directions for exploring the intervention paths of youth social psychology in the era of image socialization.